105 Beyond diagnosis: patient perception of lumbar puncture for clinical management and/or research studies. Issue 6 (27th May 2022) - Robinson, Rebecca; Kee, Rachael; Ramsay, Stephen; McKee, Jon; Kennedy, Fiona; Middleton, Rod; Rodgers, Jeff; Nicholas, Richard; McDonnell, Gavin; Hughes, Stella
Abstract : Background: Given the expanding utility of cerebrospinal fluid biomarkers in clinical practice and research studies, it may become desirable to offer repeat lumbar puncture (LP) beyond diagnosis. Using the United Kingdom Multiple Sclerosis Register (UKMSR), we assessed patient attitude to LP beyond the diagnostic stage. Design/Methods : An online questionnaire was designed and over 11, 000 patients were invited to partici- pate. For specific questions, participants indicated willingness for LP on a Likert scale (0–10). Results: Almost 2500 patients completed the questionnaire and over half had relapsing remitting MS. Of the 1089 participants on disease-modifying treatment, almost 60% indicated feeling neutral-to-agreeable to having LP to evaluate treatment efficacy or evidence of relapse. Interestingly, those indicating complete willingness represented the modal point on the scale. Respondents were only slightly less receptive to undergoing LP for research, with just under half still neutral-to-agreeable. We did not observe an influence of age or sex on willingness for LP for either indication. Conclusions: Serial LPs may become informative in evaluating for active MS throughout the disease course. We found that patients on treatment are quite agreeable to considering LP for clinical evaluation. Perhaps understandably, respondents were slightly less willing to have LP solely for research purposes. rrobinson17@qub.ac.uk